AN ANALYSIS OF THE BURIAL RITES CONFLICTS BETWEEN AGIRIAMA CHRISTIANS AND AFRICAN RELIGIOUS ADHERENTS, KILIFI COUNTY KENYA - Yaa, Margaret Dama; Joshua, Professor Stephen Muoki; wa Chidongo, Dr. Tsawe Munga (Journal of Philosophy, Culture and Religion, 2019)
Purpose: This work is an analysis of the burial rites conflicts between Agiriama Christians and adherents of African traditional religion in Kilifi County with specific reference to PEFA church in Mariakani; Kilifi County in Kenya. Burial rituals and practices vary across cultures and are often heavily influenced by religion. The objectives of the study was to establish an analysis of the burial rites conflicts between Agiriama christians and African religious adherents, Kilifi County Kenya Methodology: The study was guided by inter-faith dialogue theory and Native/non-Native relations by Jonathan Napier. The study utilized both primary and secondary sources. Secondary materials such as books, journals and articles were used to gather the necessary information. The study equally utilized some primary sources such as oral interviews, focus group discussion and participant observations. Through snow ball sampling technique seventy respondents of Agiriama community took part in the study. The study sample comprised of pastors, church elders, kaya elders and bereaved family members, based on criteria such as gender, age, social status and length of period in the church. The data was then coded and analyzed in the themes following the objectives, thus forming the chapters which make the work complete. Findings: The research findings include: the similar burial practices between the Christians and the adherents of African traditional religion, are treatment and care for the sick, prayers, unity preparing the body upon death, breaking the news of a death and burring the body. The differences include many restrictions to the close family member, categorizing death, and the funeral songs, talking to the dead, the belief that death is a rite of passage, the burial of young babies and the way the body is laid in the tomb. The Christian burial rituals lack post burial rituals unlike that for the adherents of African traditional religion. Unique contribution to theory, practice and policy: The researcher recommends further research on the post burial rituals like throwing of the death if there are any alternatives to such indigenous burial rituals which are even violating human rights. It would also be of great interest to explore further the challenges faced by those who throw the death in contrast to those who do not cleanse their homes nor throw the death.